'The look that gropes the objects': Derrida's Photographs. Issue 1 (May 2017) - Wolfreys, Julian
Abstract : In his introduction to Copy-Archive-Signature: A Conversation on Photography published in 2009, Gerhard Richter observes that while photography is concerned, 'like deconstruction', with 'questions of presentation, translation, techné, substitution, deferral, dissemination, repetition, iteration, memory, inscription, death, and mourning', relatively little attention has been given to those texts of Derrida's that specifically address photography and the work and thought of the photograph: 'Aletheia', Rights of Inspection, Athens, Remains, to name the most obvious. Things have changed a little since 2009, but it remains the case that photography, with its strange logic and uncanny temporalities, situates itself in Derrida's publications as, possibly, the most performative of tropes in Derrida's writing. As Richter argues, it is available to our view as a 'metalanguage', through which all other questions are brought into focus. This paper therefore focuses on the photograph: the photograph in Derrida's writings and photographs of Derrida.